2019
DOI: 10.1371/journal.pone.0212036
|View full text |Cite
|
Sign up to set email alerts
|

Combining liver stiffness with hyaluronic acid provides superior prognostic performance in chronic hepatitis C

Abstract: BackgroundNon-invasive methods are the first choice for liver fibrosis evaluation in chronic liver diseases, but few studies investigate the ability of combined methods to predict outcomes.Methods591 chronic hepatitis C patients with baseline liver stiffness (LSM) by FibroScan and hyaluronic acid measurements were identified retrospectively. The patients were grouped by baseline LSM: < 10kPa, 10–16.9kPa, and 17-75kPa. Primary outcomes were all-cause mortality and liver-related mortality, analyzed using cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The primary outcomes of interest were HCC, overall mortality, and liver-related mortality in 21[ 11 , 13 - 15 , 29 - 44 , 49 ], 12[ 3 , 12 , 17 - 24 , 38 , 46 ], and 10[ 16 , 18 , 20 , 21 , 25 , 27 , 28 , 45 , 47 , 48 ] studies, respectively. Twelve studies selected HD or a compound of LREs as relevant outcome(s)[ 12 , 17 - 21 , 23 , 24 , 26 , 38 , 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcomes of interest were HCC, overall mortality, and liver-related mortality in 21[ 11 , 13 - 15 , 29 - 44 , 49 ], 12[ 3 , 12 , 17 - 24 , 38 , 46 ], and 10[ 16 , 18 , 20 , 21 , 25 , 27 , 28 , 45 , 47 , 48 ] studies, respectively. Twelve studies selected HD or a compound of LREs as relevant outcome(s)[ 12 , 17 - 21 , 23 , 24 , 26 , 38 , 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies enrolled patient cohorts with HCV and human immunodeficiency virus co-infection[ 12 , 16 , 18 , 21 , 22 , 24 - 28 , 45 ]. Fifteen reports included only patients who were successfully treated, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In HCV-coinfected persons with HIV, the risk of liver-related death increased 5-fold for patients with HA > 75 ng/mL and 30-fold for patients with HA > 250 ng/mL, compared to patients with normal HA [48]. Combining liver stiffness by FibroScan with HA ≥ 200 ng/mL provides superior prognostic performance to detected liver-related mortality in chronic hepatitis C [49].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hansen et al [ 32 ] followed 591 patients with chronic hepatitis C for a median of 46.1 months and found that cirrhotic complications, defined as first episode of HCC or decompensated cirrhosis, occurred almost exclusively in patients with a baseline LSM of 17 kPa, with a negative predictive value of 98.0%.…”
Section: Discussionmentioning
confidence: 99%